Self-reported reasons for reducing or stopping antidepressant medications in primary care: thematic analysis of the diamond longitudinal study. (27th February 2023) - Coe, Amy; Gunn, Jane; Fletcher, Susan; Murray, Elizabeth; Kaylor-Hughes, Catherine
Abstract: Background: Current treatment guidelines advise that the deprescribing of antidepressants should occur around 6 months post-remission of symptoms. However, this is not routinely occurring in clinical practice, with between 30% and 50% of antidepressant users potentially continuing treatment with no clinical benefit. To support patients to deprescribe antidepressant treatment when clinically appropriate, it is important to understand what is important to patients when making the decision to reduce or cease antidepressants in a naturalistic setting. Aim: The current study aimed to describe the self-reported reasons primary care patients have for reducing or stopping their antidepressant medication. Methods: Three hundred and seven participants in the diamond longitudinal study reported taking an SSRI/SNRI over the life of the study. Of the 307, 179 reported stopping or tapering their antidepressant during computer-assisted telephone interviews and provided a reason for doing so. A collective case study approach was used to collate the reasons for stopping or tapering. Findings: Reflexive thematic analysis of patient-reported factors revealed five overarching themes; 1. Depression; 2. Medication; 3. Healthcare system; 4. Psychosocial, and; 5. Financial. These findings are used to inform suggestions for the development and implementation of antidepressant deprescribing discussions in clinical practice.